Oral Lichen Planus: Diagnosis and Management - Waal, Isaäc van der (Journal of Dentistry Indonesia, 2015)
Oral lichen planus (OLP) is a rather common oral disease, mainly affecting adults, occurring more often in women than in men. The etiopathogenesis is still unclear. The diagnosis may be cumbersome, even in the presence of a biopsy. In addition, there are several lesions that may resemble lichen planus (lichenoid lesions) both clinically and histopathologically. Treatment of OLP can only be symptomatic and usually consists of topical application of corticosteroids. The disease is characterized by remissions and exacerbations and may persist in some patients lifelong. There is an ongoing debate in the literature as whether OLP is a potentially malignant disease. Because of this uncertainty, annual follow-up is advised.